(untitled) - Glatthorn, Allan A. (New York, 1986)
The book is organized around the leadership experiences of the assistant superintendent, and it contains a wealth of guiding rubrics, figures, images, and illustrations. In addition to providing well-integrated, step-by-step problem solving guidance, it remains a theoretically sophisticated, cutting-edge integration of curriculum theory and leadership practice
Keywords: Curriculum planning,Education, elementary; Curricula; United States,United States